Cost Oriented Renewable Energy Source Solution: Design and Modeling of Photovoltaic Systems on the Innovative Campus UBT. Issue 39 (2022) - Bula, Ines; Syla, Festim; Kopacek, Peter; Hajrizi, Edmond; Bula, Edin
Abstract: Electricity and all its forms, are an irreplaceable way of supplying with electricity to all engineering systems. One of the forms of electricity that has revolutionized the last 30 years is Solar Energy, where as such it has proven to be a cost oriented solution of producing energy. This paper examines all the steps, advantages and the most modern photovoltaic technologies. "How ready is Kosovo for solar energy p roduction?" this question that finds the answer within this paper. Part of this paper is the modeling and design of photovoltaic systems on the Innovative Campus UBT, which can be considered as a guide for solar system installers. After presenting the efficiency of the installation of photovoltaic systems on the Innovative Campus of UBT, it seems clear that the needs of state and citizen awareness at the same time on the true purpose of installing solar systems, contributing to the overall social well-being. The application of solar systems in institutions and the benefit that the application of this technology brings not only in financial aspects, as it is presented in the case of the Innovative Campus UBT study, but also the most important aspects are environmental aspect, making a drastic reduction of the emission of polluting elements in nature.